CAAT/enhancer binding protein is able to bind to ATF/CRE elements. - Bakker, O (1991)
The transcription factor C/EBP is known to be able to bind to two different classes of sites, a CAAT-box and one present in a number of viral enhancers. In this paper we show using band-shift assays, methylation interference and footprinting that C/EBP is also able to bind with high affinity to ATF/CRE sites. Competition with mutant ATF sites and methylation interference indicate that C/EBP may be able to bind to the ATF/CRE sites by virtue of their homology to the enhancer core elements. Furthermore, we show that C/EBP is able to direct transcription from this site in transient transfection experiments and that mutations in the ATF binding site that impair DNA binding also effect the ability of C/EBP to stimulate transcription.